Solve the equation. y′′−6y′+9y=0 ; y(0)=2,y′(0)=−4
a. using differential equation method
b. using Laplace transformation method
a. Characteristic equation:
"{k^2} - 6k + 9 = 0"
"{(k - 3)^2} = 0"
"{k_1} = {k_2} = 3"
Then
"y = {C_1}{e^{3x}} + x{C_2}{e^{3x}} \\Rightarrow y' = 3{C_1}{e^{3x}} + {C_2}{e^{3x}} + 3x{C_2}{e^{3x}}"
"y(0) = 2,\\,y'(0) = - 4 \\Rightarrow \\left\\{ {\\begin{matrix}\n{{C_1} = 2}\\\\\n{3{C_1} + {C_2} = - 4}\n\\end{matrix}} \\right. \\Rightarrow {C_1} = 2,\\,{C_2} = - 10"
Then
"y = 2{e^{3x}} - 10x{e^{3x}}"
Answer: "y = 2{e^{3x}} - 10x{e^{3x}}"
b. Moving from originals to images:
"y \\to Y"
"y' \\to pY - y(0) = pY - 2"
"y'' \\to {p^2}Y - py(0) - y'(0) = {p^2}Y - 2p + 4"
Then
"{p^2}Y - 2p + 4 - 6\\left( {pY - 2} \\right) + 9Y = 0"
"Y\\left( {{p^2} - 6p + 9} \\right) = 2p - 4 - 12"
"Y = \\frac{{2p - 16}}{{{p^2} - 6p + 9}} = \\frac{{2p - 16}}{{{{(p - 3)}^2}}} = \\frac{2}{{p - 3}} - \\frac{{10}}{{{{(p - 3)}^2}}}"
"Y \\leftarrow y"
"\\frac{1}{{p - 3}} \\leftarrow {e^{3x}}"
"\\frac{1}{{{{\\left( {p - 3} \\right)}^2}}} \\leftarrow x{e^{3x}}"
Then
"y = 2{e^{3x}} - 10x{e^{3x}}"
Answer: "y = 2{e^{3x}} - 10x{e^{3x}}"
Comments
Leave a comment